PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT, JOB DEMANDS, DAN BURNOUT TERHADAP KEPUASAN KERJA KARYAWAN - Ardari Ara Zirinita; M. Farid Wajdi (JURNAL LENTERA BISNIS, 2024)
This study aims to analyze the effect of perceived organizational support, job demand, and burnout on employee job satisfaction at the Regional Office of the Directorate General of Taxes in Central Java II. This study uses a quantitative approach with data collection techniques through online questionnaires using Google Form. The research sample is determined by the purposive sampling method, and the data are analyzed using the SmartPLS 3.3 software. The results showed that perceived organizational support had a positive and significant influence on employee job satisfaction with a T-Statistic value of 6,754 (p <0.05). Job demand also has a positive and significant influence on employee job satisfaction with a T-Statistic value of 3,687 (p <0.05). In addition, burnout has a positive and significant influence on employee job satisfaction with a T-Statistic value of 3,713 (p <0.05). This study provides new insights on the importance of managing organizational support, workload, and burnout conditions to increase employee job satisfaction.